Association between physical activity and risk of prevalent psoriasis: A MOOSE-compliant meta-analysis. Issue 27 (July 2018) - Zheng, Qi; Sun, Xiao Ying; Miao, Xiao; Xu, Rong; Ma, Tian; Zhang, Ya Nan; Li, Hong Jin; Li, Bin; Li, Xin
Abstract : Abstract: Psoriasis is a common chronic relapsing immune-mediated inflammatory disease, whose prevalence has increased in recent years. Some physicians believe that physical activity is associated with numerous health-related benefits in adults with dermatoses. While numerous studies have suggested an association between psoriasis and physical activity, others have yielded contradictory results. The aim of our study was to evaluate the association between the level of physical activity and prevalence of psoriasis. A comprehensive search of the literature was performed from January 1970 to February 2017 using EMBASE, MEDLINE, and the Cochrane Central Register of Controlled Trials electronic databases. Studies published in English were reviewed to identify the contribution of intensity of physical activity on the prevalence of psoriasis. The search strategy yielded 1100 relevant studies, among which 13 observational studies were included. We found that patients with psoriasis exercise significantly less vigorously than controls (relative risk [RR]: 0.76; 95% confidence interval [CI]: 0.67–0.85; P < .00001). Predominantly, these patients exercised at moderate intensity (RR: 0.40; 95% CI: 0.18–0.90; P = .03). Some patients had lesser degree of movement, and some exercised strenuously. There were no significant differences observed in the intensity of exercise performed by controls (RR: 0.90; 95% CI: 0.46–1.77; P = .76). The 3 studies found the frequency of regular exercise differed significantly between patients with psoriasis and controls (RR: 0.88; 95% CI: 0.82–0.95; P = .0007). Different severities of psoriasis have different influences on patients' physical activity levels. Patients with a higher proportion of psoriatic lesions and self-awareness were associated with lower-intensity exercises. Our meta-analysis highlights the fact that intense physical activity may lower the prevalence of psoriasis.